Determinación de un pie de cría del caracol pomacea canaliculata, (mesogastropoda, ampullaridae) utilizando hojas de tomate como base alimenticia, bajo condiciones de invernadero. - Villalba Avilés, Cristopher Renato (2013)
In the world is sown annually, approximately 129.2 million hectares of rice production reached around 477.4 million metric ton world. In Ecuador the first grain rice is the most important in human nutrition, in which employ about 140,000 people who are 18% of the economically active population engaged in agriculture, currently our country are planted approximately 420,000 hectares, being distributed production, 60% in the Guayas, Los Ríos, El Oro and Loja. The objective of this research was to determine the diets in the leaves of tomato apple snail Pomacea canaliculata. The work was conducted on the premises of the Lord Renato Villalba located on street Juan Verdesoto and Longitudinal sector Cristo del Consuelo. We investigated eight diets tomato leaves with four replications in plots or contenner of 0.8 m2, which were distributed in a complete block design random. For the evaluation of means used the Tukey test at 5 % probability. Cycle was evaluated: incubation time, color of eggs, egg size, egg weight, length of development phases adult life, color of egg mass, number of eggs per mass and volume weekly food consumption.